Integration of Parents’ Roles in Designing Fraction Didactic Designs Using DDR in Elementary Schools - Entit Puspita; Yenyen Hendrayani; Siti Fatimah; Al Azhary Masta; Muhammad Taqiyuddin (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
This study explores the dynamics of parental involvement and the challenges in facilitating understanding of fraction concepts as an integral part of the prospective analysis phase within the Didactic Design Research (DDR) framework. The investigation focused on mapping the reality of home support that risks triggering secondary learning obstacles for students. Using a descriptive qualitative methodology, data were collected through testing and in-depth interviews with parents and elementary school teachers in Sukabumi Regency. The study results revealed two main obstacles: limited time due to professional workload and limited conceptual understanding of the mathematical material. The phenomenon in the field shows a tendency for parents to rely on learning patterns that emphasize mechanical memorization and procedural shortcuts, systematically reinforcing epistemological obstacles in children. These findings underscore the importance of formulating a didactic design that bridges classroom learning with practical guidance accessible to families. Synchronizing the identification of parental problems and the design of materials is a strategic foundation for realizing a learning model that is realistic, functional, and aligned between formal institutions and the home environment.